HERACLITUS, PARMENIDES AND ZENO: : THE MATHEMATICAL HISTORY OF THE REDUCTIO AD ABSURDUM - Anna Sapunaru, Raquel; Frederico G. Santiago, Douglas; L Porto , Anderson; R. Moraes , Beatriz; M. Verissimo, Luísa (Journal of Interdisciplinary Debates, 2022)
This article tells the story of the proof known as reductio ad absurdum, through the biographies of Heraclitus, Parmenides and his disciple Zeno. Emphasis is placed on Zeno’s paradoxes and some classic demonstrations of modern mathematics, in which proof by reductio ad absurdum is used widely. In other words, we intend to discuss the logical-mathematical history of reductio ad absurdum, from the birth of logic in Heraclitus, Parmenides and Zeno and ipso facto to establish a relationship between Heraclitus, Parmenides and Zeno and modern mathematical logic. The method used was the bibliographic, referring mainly to secondary sources due to the strictly theoretical nature of the subject.